UMA ABORDAGEM PARA A JUNÇÃO DE ONTOLOGIAS E SUA UTILIZAÇÃO NO DESENVOLVIMENTO DE ONTOLOGIAS DE APLICAÇÃO - Silva, Antonio Fhillipi Maciel (2014)
The reuse of ontologies is a process in which the existing ontological knowledge is used as input to generate new ontologies, in order to reduce costs and increase the quality of the final product. However, techniques for building ontologies do not address reuse satisfactorily, even though this is an indispensable phase in ontology engineering. This work presents OntoJoin, a process for joining ontologies which employs lexical, structural and relational similarity analysis as mapping mechanisms. These mechanisms are responsible for identifying correspondences between elements of two ontologies given as input. These mechanisms are used to match similar elements, thus resulting in a new ontology generated from reuse. The set of mechanisms use "Lexical Comparison", which performs a comparison between the labels of the terms of the ontology elements; "Structural Comparison", which performs an analysis of the concepts and their respective hierarchical structure; "Relational Comparison", which performs an analysis of concepts, their properties and non-taxonomic relationships; and "Index of Terms", which alter the concepts for their better representation, is the main feature that gives OntoJoin the potential to achieve greater effectiveness at the junction of ontologies compared with previously proposed techniques. An experimental evaluation has been performed according two procedures based on the principle of comparing the joint ontology against a reference one. This experiment consisted in measuring with recall and precision the effectiveness of the process for combining two ontologies in the tourism and sales domains. The preliminary results demonstrate the feasibility of the proposed process in joining ontologies.